2007
DOI: 10.1007/s00280-007-0635-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microtubule activity of tubeimoside I and its colchicine binding site of tubulin

Abstract: Background Tubeimoside I (TBMS1) was isolated from the tubers of Bolbostemma paniculatum (Maxim.) Franquet. TBMS1 shows potent anti-tumor activity. The present study was conducted to investigate the anti-microtubule role of TBMS1 and its binding site of tubulin. Methods Cell growth inhibition was measured by MTT after treatment with TBMS1. Uptake kinetics of TBMS1 by human nasopharyngeal carcinoma CNE-2Z cell line (CNE-2Z) was assayed by HPLC. Microtubule protein (MTP) was prepared from porcine brain through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Furthermore, the cells become round-shaped and poorly adhered to the cultured plates while the control group cells showed a typical polygonal and cobblestone monolayer appearance and remained firmly attached to cultured plates (data not shown). The results indicated that TBMS1 induced growth inhibition of A375 cells, in addition to other type of cancer cells previously reported including A549 lung cancer cells (Zhang et al, 2011), HeLa cervical cancer cells (Xu et al, 2009), and nasopharyngeal carcinoma CNE-2Z (Ma et al, 2008;Weng et al, 2003).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the cells become round-shaped and poorly adhered to the cultured plates while the control group cells showed a typical polygonal and cobblestone monolayer appearance and remained firmly attached to cultured plates (data not shown). The results indicated that TBMS1 induced growth inhibition of A375 cells, in addition to other type of cancer cells previously reported including A549 lung cancer cells (Zhang et al, 2011), HeLa cervical cancer cells (Xu et al, 2009), and nasopharyngeal carcinoma CNE-2Z (Ma et al, 2008;Weng et al, 2003).…”
Section: Resultssupporting
confidence: 59%
“…Tubeimoside-1 (TBMS1), a triterpenoid saponin has been reported to have wide spectrum of biological effects, including anti-inflammatory, anti-tumorigenic and anti-HIV activities (Yu et al, 1994;Yu et al, 1992). Furthermore, TBMS1 has anti-proliferative effect and induced apoptosis in cancer cells such as lung cancer (Zhang et al, 2011), cervical cancer (Xu et al, 2009), nasopharyn-geal carcinoma (Ma et al, 2008;Weng et al, 2003) and leukemia HL-60 cells (Yu et al, 1996). However, the cytotoxic effects of TBMS1 on melanoma and its mechanism were still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The method was performed according to earlier publications (Ma et al, 2007). Each 0.5 ml reaction contained 0.1 M MES (pH 7.0 with NaOH in 1 M stock solution), 0.5 mM MgCl 2 , 1 mM of tubulin [ 3 H]colchicine (5 mM), and the indicated concentration of different drugs (1 and 5 mM combretastatin A-4-phosphate (CA4P); 5 and 50 mM 2-methoxyestradiol (2ME 2 ); 5 and 50 mM P529).…”
Section: Effect Of P529 On Colchicine Binding To Tubulinmentioning
confidence: 99%
“…The assay was carried out based on previous procedures with some modifications (Ma et al, 2008). Briefly, a drug/DMSO-tubulin preincubation, without GTP, was performed for 15 min at 0°C in ice.…”
Section: Tubulin Polymerization Assaymentioning
confidence: 99%